Agribisnis Ayam Potong Berbasis Probio Fm Plus Di Politeknik Pertanian Negeri Kupang - Helda Helda; Catootjie L Nalle; Bachtarudin Badewi (Jurnal SOLMA, 2019)
Broilers are meat type chickens which are having tender meat and can be harvested in aerly stage of age (28 d) so that can recoup quickly. Broiler agribusines has been conducted since 2005 in polytechnic of Agricuture Kupang, started with very small scale. It has been well known that chicken excreta is one of the contributors in environmental polution due to the emisión of ammonia (NH3). Ammonia arena lokasi kandang verada di lingkungan kampus. Ammonia is the result of nitrogent decomposition in chicken excreta, such as uric acid undigested protein and non protein nitrogent. Thus, the effort to reduce the ammonia polution in by using probiotics. In PPUPIK activity, Probio FMplus, which is a modification product of In Probio-FM in Jambi University, is used for boiler rearing. The main comodity of PPUPIK in Polytechnic of Agriculture is broiler chickens. Type of housing used is floor pens with the capacity 1,000 birds and 7,000 birds in two different location. Additional products from PPUPIK are probiotics (Probio Fmplus), processing products (ie. nuggets), and organic fertilizer which is fermented using Probio FMplus. The positive impacts of PPUPIK activities are the improvement of student competency, supporting tri dharma activities, and as a place for competent test for senior vocational students.